A selenoprotein T‐derived peptide protects the heart against ischaemia/reperfusion injury through inhibition of apoptosis and oxidative stress. (17th April 2018) - Rocca, C.; Boukhzar, L.; Granieri, M. C.; Alsharif, I.; Mazza, R.; Lefranc, B.; Tota, B.; Leprince, J.; Cerra, M. C.; Anouar, Y.; Angelone, T.
Abstract: Aim: Selenoprotein T (SelT or SELENOT) is a novel thioredoxin‐like enzyme whose genetic ablation in mice results in early embryonic lethality. SelT exerts an essential cytoprotective action during development and after injury through its redox‐active catalytic site. This study aimed to determine the expression and regulation of SelT in the mammalian heart in normal and pathological conditions and to evaluate the cardioprotective effect of a SelT‐derived peptide, SelT43‐52(PSELT) encompassing the redox motif which is key to its function, against ischaemia/reperfusion(I/R) injury. Methods: We used the isolated Langendorff rat heart model and different analyses by immunohistochemistry, Western blot and ELISA. Results: We found that SelT expression is very abundant in embryo but is undetectable in adult heart. However, SelT expression was tremendously increased after I/R. PSELT (5 nmol/L) was able to induce pharmacological post‐conditioning cardioprotection as evidenced by a significant recovery of contractility (dLVP) and reduction of infarct size (IS), without changes in cardiac contracture (LVEDP). In contrast, a control peptide lacking the redox site did not confer cardioprotection. Immunoblot analysis showed that PSELT‐dependent cardioprotection is accompanied by a significant increase in phosphorylated Akt, Erk‐1/2 and Gsk3α‐β, and a decrement of p38MAPK. PSELT inhibited the pro‐apoptotic factors Bax, caspase 3 and cytochrome c and stimulated the anti‐apoptotic factor Bcl‐2. Furthermore, PSELT significantly reduced several markers of I/R‐induced oxidative and nitrosative stress. Conclusion: These results unravel the role of SelT as a cardiac modulator and identify PSELT as an effective pharmacological post‐conditioning agent able to protect the heart after ischaemic injury.